Fluorescent Probes from Aromatic Polycyclic Nitrile Oxides: Isoxazoles versus Dihydro‐1λ3, 3, 2λ4‐Oxazaborinines. Issue 6 (13th June 2019) - Moiola, Mattia; Bova, Antonio; Crespi, Stefano; Memeo, Misal G.; Mella, Mariella; Overkleeft, Herman S.; Florea, Bogdan I.; Quadrelli, Paolo
Abstract: Anthracenenitrile oxide undergoes 1, 3‐dipolar cycloaddition reaction with propargyl bromide affording the expected isoxazole as single regioisomer, suitably synthetically elaborated and functionalized with a protected triple bond. The introduction of a bromine atom at the position C10 of the anthracene moiety allows for inserting a variety of aromatic and heterocyclic substituents through Suzuki coupling. A two‐way synthetic route can lead to simple isoxazole derivatives or, after N−O bond reductive cleavage and BF3 complexation, enamino ketone boron complexes. The photophysical properties of both the substituted isoxazoles and the corresponding boron complexes were investigated to show the potentialities for the employment as fluorescent tags in imaging techniques. The quite good quantum yield values confirm the suitability of these compounds in the cellular environment. Scope and limitations of the methodology are discussed. Abstract : Isoxaxole or boron complex ? A two‐way synthetic route leads to simple isoxazole derivatives or, after N−O bond reductive cleavage and BF3 complexation, enamino ketone boron complexes. The photophysical properties of both substituted isoxazoles and corresponding boron complexes have been investigated to show the potentialities for the employment as fluorescent tags in imaging techniques.